Gene expression profiling of oxidative and anti‐oxidative genes in keratoconus patients - Sharma, Shivam; Singh, Lata; Kashyap, Seema; Sen, Seema; Sharma, Namrata (Acta ophthalmologica (Oxford, England), 2025)
Aims/Purpose: Keratoconus (KC) is thinning of corneal stroma & irregular astigmatism, resulting in diminution of vision. Despite its prevalence, the underlying etiology is poorly understood. Emerging evidence suggests a dysregulation of oxidative balance and mitochondrial function in KC corneas. Therefore, our study conducted the gene expression profiling of oxidative stress‐based genes in KC patients. Methods: This was a prospective study for a period of two years. Fifty KC patients were recruited in this study. Demographic and clinical details were recorded. RNA was isolated from all the corneal samples and their cDNA was synthesized. mRNA expression levels of oxidative stress‐based genes (PRDX6, SCARA3, FOXC1, HMOX1, SOD2, GPX4, NRF2, NOX4) were measured by quantitative real‐time PCR (qRT‐PCR) in corneal tissues of KC patients and healthy controls. The relative gene expression was calculated using the ΔΔCt method. Results: The study included 50 keratoconus patients (mean age: 25.5 ± 12.34 years; 65% male) and 25 control subjects (mean age: 27.2 ± 11.26 years; 55% male). The severity of keratoconus among patients varied from moderate to advanced stages. In our study, qRT‐PCR analysis revealed significant differential expression of the oxidative and antioxidative genes in keratoconus tissues compared to the control samples. SCARA3, FOXC1, HMOX1, SOD2, GPX4, NRF2 were found downregulated, PRDX6 was upregulated in all the cases. NOX4 showed variable expression patterns with upregulation in 40% cases and downregulation in remaining 60% cases. Conclusions: The study included 50 keratoconus patients (mean age: 25.5 ± 12.34 years; 65% male) and 25 control subjects (mean age: 27.2 ± 11.26 years; 55% male). The severity of keratoconus among patients varied from moderate to advanced stages. In our study, qRT‐PCR analysis revealed significant differential expression of the oxidative and antioxidative genes in keratoconus tissues compared to the control samples. SCARA3, FOXC1, HMOX1, SOD2, GPX4, NRF2 were found downregulated, PRDX6 was upregulated in all the cases. NOX4 showed variable expression patterns with upregulation in 40% cases and downregulation in remaining 60% cases. Keywords: Cornea, Keratoconus, Oxidative stress, Real time PCR